The Ambiguity of the Standard of Good Faith and Prudence in the Accountability of Directors that Causes Bankruptcy of Limited Liability Companies Based on the Fiduciary Duty Principle - Hendro Widodo; Riswadi Riswadi (Greenation International Journal of Law and Social Sciences, 2025)
Based on the idea of fiduciary obligation, this paper investigates the vagueness of the requirements of good faith and caution in the accountability of directors under Article 97 of the Limited Liability Company Law, which causes limited liability firms to go bankrupt. As the company's governing body, the board of directors has a duty to run the business responsibly, professionally, and in good faith. However, in practice, there is often ambiguity regarding the limits of responsibility, criteria for negligence, and the definition of conflict of interest. A normative legal analysis indicates a legal vacuum in Article 97, particularly regarding objective standards of good faith, mechanisms for proving negligence, and loss prevention procedures, allowing directors to avoid liability even though their actions are detrimental to the company. Using a comparative legal approach and interpretation of the fiduciary duty doctrine, this study emphasizes the need for legal reform through the formulation of clearer criteria regarding the fiduciary obligations of directors, standards of prudence, loss prevention mechanisms, and regulations regarding conflicts of interest.